Development of a Smart Thermostat Controller for Direct Load Control Based Demand Response Applications - Yener, Baris; Erenoglu, Ayse Kubra; Sengor, Ibrahim; Erdinc, Ozan; Tascikaraoglu, Akin; Catalao, Joao P. S. (IEEE, 2019)
The demand side, which was formerly considered as an inelastic part of the power system operation, has recently been evaluated as a source of flexibility to enhance the effectiveness and economy of power system operation. Several real world examples and literature studies exist to evaluate the contribution of demand side flexibility in power system operation in this manner. Accordingly, in this study, a smart thermostat controller for direct load control based demand response applications for controlling the thermostatically controllable loads by Thermostat Set-point Control Mechanism (TSCM) method is developed differently from the existing studies, where few of them have considered the real world applicability requirements of such concepts. The concept has been experimentally verified under different case studies.
Keywords: demand response; direct load control; smart thermostat controller; thermostatically controllable appliances; CONTROL ANCILLARY SERVICES; FREQUENCY; Computer Science; Energy & Fuels